The Tipping Point to Terrorism: Involvement in Right-Wing Terrorist Groups in the United States - Reeser, Anne M. Stacey (2011)
This dissertation focuses on right-wing terrorism (RWT) in the United States perpetrated by adherents to the White Supremacist Movement (WSM). In depth case history data were collected using a variety of sources and analyzed on 66 federally indicted WSM terrorists representing 10 different terrorist organizations in the United States from 1980-2002. The primary means of analysis was a qualitative case analysis using narrative data to uncover what influences an individual to become involved in a terrorist group. Specifically, I analyzed the influences of: 1) structural components, 2) family dynamics, and 3) non-familial relationships on the involvement process. Results from this study can provide valuable theoretical and practical implications to understanding terrorists and terrorist groups